How Cultural Capital Affects Student Academic Achievement - Ge, Ting; Wu, Chenshuo (Best Evidence in Chinese Education, 2026)
In the context of calls for educational equity and competence-focused education, the relationship between cultural capital and student academic achievement and the mechanisms influencing the relationship are key issues in the understanding of educational stratification and institutional tensions. Based on the two-session data from the China Education Panel Survey, this article analyzes how cultural capital affects student academic performance using the covariate balancing generalized propensity score method and structural equation modeling. The findings reveal that the effect of cultural capital on student academic achievement can be mediated by self-efficacy, and that the school’s preference for exam-focused education is negatively related to the positive effect of cultural capital, particularly objectified cultural capital.